Impact of Surface Roughness on Consistent Resonator Performance - Senthil Kumar Karuppannan; Naga Manikanta Kommanaboina; Adrian Nugraha Utama; Manas Mukherjee (Advanced Materials Interfaces, 2025)
Abstract Superconducting circuit‐based quantum processors are leading platforms for quantum computing. In these circuits, microwave photons are stored as qubits in ultra‐low‐loss planar resonators and non‐linear inductors formed by Josephson junctions. Resonators are typically made from high‐energy‐gap superconductors like Nb or Ta, while the junctions are made of Al. Resonators occupy much of the circuit, making defect‐free fabrication and understanding microwave energy dissipation crucial. Losses arise from noise, two‐level systems (TLS), quasi‐particles, and impurities. TLS losses dominate at operating temperatures below the critical temperature of the metal, whereas photon loss due to quasi‐particles, often stemming from grain boundaries and pinholes in the metal film, becomes more pronounced at higher photon numbers or temperatures approaching the metal's critical temperature. To mitigate these, substrate cleaning, surface control, and non‐superconducting film capping prevent oxide formation and reduce impurities. High‐frequency drives and impurities at the grain boundaries lead to nonuniform quality factors among resonators. By controlling oxygen plasma exposure to minimize surface roughness and pinhole depth, an area‐dependent quality factor is observed, which are attributed to changes in surface resistivity. This approach minimized variations in quality factors across resonators, improving uniformity in Nb‐based devices and more consistent qubit readout performance.